MANAJEMEN KEUANGAN MASJID DI KOTA BAUBAU - Dila Yusfita; Agusdiwana Suarni; Muhammad Khaedar Sahib (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2023)
This study aims to determine the financial management system of mosques in Baubau City. This study uses descriptive qualitative analysis by focusing on the mosque's financial management system. Types and sources of data used are primary and secondary data in the form of interviews, observation, and documentation. The results of research on the mosque's financial managementsystem in Baubau City showseveral things of concern, namely the system of receivingfunds and disbursing funds. Transparency in the Baubau Agung Mosque and the Islamic Center Mosque has been effective and efficient, but the Agung Keraton Buton mosque is not transparent. Mosque accountability in Baubau City is accurate, but not yet in accordance with ISAK 35 rules. As the use of mosque funds in Baubau City is used for mosque operational costs.